2022
DOI: 10.1089/tmj.2021.0148
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Digital Contact Tracing Strategy Addresses Stigma Concerns Among Individuals Evaluated for COVID-19

Abstract: Background: Conventional contact tracing approaches have not kept pace with the scale of the coronavirus disease 2019 (COVID-19) pandemic and the highly anticipated smartphone applications for digital contact tracing efforts are plagued by low adoption rates attributed to privacy concerns; therefore, innovation is needed in this public health capability. Methods: This study involved a cross-sectional, nonrepresentative, online survey in the United States of individuals tested for COVID-19. Testing survey items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This study found that 40.3% of their respondents would be interested in using such a service. In addition, respondents generally anticipated that they would notify more contacts—and notify contacts faster—if the service would be available [ 8 ]. Several studies also investigated the application of self-monitoring tools for cases and/or contacts.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that 40.3% of their respondents would be interested in using such a service. In addition, respondents generally anticipated that they would notify more contacts—and notify contacts faster—if the service would be available [ 8 ]. Several studies also investigated the application of self-monitoring tools for cases and/or contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies mainly focused on digital tools for monitoring index cases and/or contact persons’ symptoms and health status [ 11 ], or digital tools that automate the identification and notification of contact persons using GPS-location or Bluetooth signals that serve as an anonymous proxy for physical interactions between individuals [ 9 , 12 14 ]. One study found that anonymous case-initiated contact notification may mitigate citizens’ concerns regarding privacy and reduce the stigma that can hamper contact notification [ 15 ]. Another study described the use of a contact diary web-application that citizens can use to manually record contact persons daily (to reduce recall bias), share information with the PHS, and notify contact persons, via e-mail [ 11 ].…”
Section: Introductionmentioning
confidence: 99%